ANALISIS TUMBUH UMBI KENTANG (Solanum tuberossum L.) DI DATARAN RENDAH - Made Deviani Duaja (Bioplantae, 2012)
The potato cultivation in the highland area has been redistricted due to the facts of small area that suitable for potato cropping. The suitable landispurposed to be conservation practice. Therefore, inorder to increase potato yield could be established by the expansion to the lowlands area. But in the lowlands has been redistricted by the negative effects of high temperatures for tuber formation and the lack of well adapted variety. Those limitations could be overcome by finding the well variety that could be adapted in the lowland. The experiment aim is to observe the adapted cultivars. The treatments arecultivars: Granola I (G2), DTO 28, Atlantik andtwo varieties, Granola II (G3) and Eigenheimer (highed land at Jambi Provincial). The parameter to evaluate is number of tubers, tuber growth rate, sinc strength and source strength. This experiment used Randomized Block Design (RBD). The results shows that the highest source strength, sinc strength, tuber weight per plant, numbers of tubers, and tuber growth rate was achieved at variety Granola II. Key words: sinc, source, tuber formation.